Markt und Organisation: Programmatische Überlegungen zur Wirtschafts- und Unternehmensethik - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2008)
Dieser Beitrag skizziert das ordonomische Forschungsprogramm einer ökonomischen Theorie der Moral und stellt die Grundzüge einer mit dieser Methode arbeitenden Wirtschafts- und Unternehmensethik vor: Die Ordonomik versteht sich als eine rational-choice- basierte Analyse der Interdependenz von Sozialstruktur und Semantik. Sie betreibt Ethik mit ökonomischer Methode. Gestützt auf die sozialstrukturelle Analyse sozialer Dilemmata, besteht die theoretische Grundfigur in einer orthogonalen Positionierung zu den geläufigen Trade-Off-Vorstellungen eines Wertekonflikts zwischen Eigeninteresse und Moral. Die Wirtschaftsethik fragt, wie sich das Eigeninteresse wirtschaftlicher Akteure für moralische Anliegen in Dienst nehmen lässt. Die Unternehmensethik fragt genau spiegelbildlich, wie sich moralische Bindungen für das wirtschaftliche Eigeninteresse in Dienst nehmen lassen. Aus einer solchen Perspektive erscheint Moral als ein Produktionsfaktor. – – This paper argues that the ordonomic research program of an economic theory of morality provides important insights for the fields of both economic ethics and business ethics. Ordonomics is conceived here as a rational-choice based analysis of (the interdependencies between) social structure and semantics. As such, the ordonomic perspective provides an economic—i.e. rational-choice based—approach to ethics. Conventional semantics often assumes a fundamental trade-off between self-interest and morality. Grounded in the institutional analysis of social dilemmas, the ordonomic concept of an orthogonal position transcends this trade-off thinking. The article claims that there are two complementary perspectives on how self-interest and morality can be made compatible: Economic ethics is about the ethics of the economic system. It addresses the question as to how individual self-interest can be harnessed to further moral objectives. Business ethics is about the ethics of the business firm. It addresses the question of how moral commitments can help to better realize the firm's economic self-interest. Viewed in this light, morality can serve as a powerful factor of production.
urn:nbn:de:gbv:3:2-6555
Keywords: A12; A13; D02; D63; D74; M14; 330; Wirtschaftsethik; Unternehmensethik; Ordonomik; ökonomische Theorie der Moral; Corporate Citizenship; Ordnungsverantwortung; Nachhaltigkeit; Sozialstruktur; Semantik; Markt; Organisation; Moralkommunikation; economic ethics; business ethics; ordonomics; economy theory of morality; corporate citizenship; ordo-responsibility; sustainability; social structure; semantic; market; organisation; moral communication; Wirtschaftsethik; Unternehmensethik; Sozialstruktur; Rationalität; Regulierung; Wirtschaftsphilosophie